CLINICAL CONFERENCE AS A FORM OF INDEPENDENT WORK OF INTERNS - T.P. Skripnikova; M.V. Khrebor; Yu.I. Silenko (Ukrainian Medical Stomatological Academy, 2015)
The main objective of higher education is the formation of a creative personality specialist able to selfdevelopment, self-education, and innovation. Meeting this challenge requires the focus on active methods of acquiring knowledge, creativity, transition from the current to the individualized training tailored to the needs and abilities of the individual. Solution of this problem requires orientation on the active methods of acquiring knowledge, creativity, transition from the current to the individualized training tailored to the needs and abilities of the individual. An important role takes place an independent academic work, which is divided into class and outside of classroom. Self-study becomes at postgraduate stage of raining, particularly in the preparation of interns. Thus, it is necessary to form the ability to self-teach creatively apply the knowledge, methods of adaptation to the profession in the modern medical world. The purpose of the article was the description of the new form of self-study doctors -interns called Clinical Conference. Clinical conferences carried out according to the thematic plan of discipline "Dentistry". Clinical conference is held with all groups of interns and is a special design of training aimed at enhancing, strengthening and improving the knowledge, skills formation of arguments to defend their point of view, to answer questions from the audience, listening to others, asking questions. Clinical conferences are held monthly during the school year at the Department of postgraduate education of dentists. At each conference, no more than three reports of interns on topical issues of dentistry (based on 1 hour of the conference) should be prepared. The organization of clinical conference of the following algorithm is used: 1. Opening remarks of the presiding that defines a list of questions that reveal the theme of the conference. 2. Reports. Questions and answers after each presentation. 3. Discussion of the reports (review and assessment reports). 4. The results of the conference. A report is conducted by a team of interns under the supervision of a teacher. The proposed type of work is characterized by high motivation, because the doctor - intern understands its usefulness. The results will be actively used him and his colleagues in their professional activities, and can also be used in publications. Motivational factor determines the teacher as a professional. The teacher is a model for the student as a creative person. The teacher should help the student to discover their creative potential, to determine its prospects for internal growth. Scientific, academic style is used for the presentation of the report. All messages have a common structure. Traditionally, any scientific report consists of three parts: introduction, main body and conclusion. The best reports are advised to be represented at the annual final scientific conference of interns, masters and clinical residents, conducted at the academy in May or June. According to the results of all reports prepared theses which will be published in the conference proceedings. The positive evaluation of the work was done by colleagues promotes the professional and scientific affirmation of interns. Thus, the introduction of such a form of independent work of interns, as participation in the conference, promotes the formation of their personal and professional independence, broadens the mind, improves the intellectual level, an incentive for the formation of high internal positive motivation, and raises the level of their personal self-esteem.